Sam Fox library orchestra folio No.1, piano - MILES, Walter E. [et.al] (Sam Fox Pub., 1912)
SparkletsnBasket of rosesnBleanornValse DanseusenA garden dancenBowl of pansiesnAt sunsetnDancing leavesnWater LiliesnMon plaisirnIn poppylandnDream of the flowers